Modeling hybrid polymer ball bearing with elastoplastic contact model and its nonlinear dynamic response - Dogan, Burcu Kucukoglu; Dal, Abdurrahim; Karacay, Tuncay (Springer, 2025)
The dynamic behavior of a polymer ball bearing system is mostly dependent on the contact characteristics among the ball and the races of the bearing. Although the well-known Hertz contact theory is widely used to model contacts in conventional bearings, it cannot be directly applied to polymer bearings due to the viscoelastic characteristics of the polymer structures. In this study, contacts in the polymer hybrid ball bearing are modeled using elastoplastic characteristics. The contact between inner/outer raceways and the ball is solved in elastic, elastoplastic, and plastic characteristics regions depending on the polymer structure and the loads. Then, two-degree of freedom rigid rotor-bearing system is simulated under different rotational speeds as well as different rotor weights. In order to investigate the nonlinear nature of the dynamic response, results are analyzed with different methods such as waterfalls, bifurcation diagrams, phase diagrams and Poincar & eacute; sections. The characteristic changes in the contact form elastic to elastoplastic regions are observed as a new peak in the time history that may lead to chaotic motion. A similar response is also seen when a single ball-race contact is in the elastoplastic region. The results are helpful to understand the cause and result of contact in a viscoelastic contact condition.
Keywords: Polymer hybrid ball bearing; Elastoplastic contact; Nonlinear dynamic